An Overview of the ULU Gold Deposit, High Lake Volcanic Belt, Nunavut, Canada - E. Flood; P. Kleespies; M. Tansey; H. Muntanion; R. Carpenter (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
Abstract - BHP Minerals discovered the Archean lode gold ULU deposit on the western margin of the High Lake Volcanic Belt in 1989. The greenschist to amphibolite facies mafic volcanic and sedimentary rocks on the property are folded into a 5 km-long anticline. There is a close spatial association of Au-As zones to the trace of this F2 ULU anticline. The largest of these auriferous zones, the Flood zone, is localized at the core of the fold. The southeast-trending Flood zone consists of several anastomosing lenses that have been traced for 435 m on surface. Overall, it dips steeply (70° to 80°) to the southwest and has been intersected to depths below 600 m. The hosting high-iron tholeitic basalt displays a lower amphibolite mineral assemblage of ferrohornblende + plagioclase + ilmenite with accessory quartz and epidote. Alteration minerals include biotite, chlorite, hornblende, actinolite-tremolite, and potassium feldspar (microcline) with minor calcite, epidote, tourmaline, and titanite. The highest gold values occur where brecciated basaltic wall-rock clasts are replaced by acicular arsenopyrite + quartz + K-feldspar. BHP Minerals completed 54,783 m of both exploration and resource development drilling before selling the ULU property to Echo Bay Mines in 1995. Development of ULU as a satellite deposit to Echo Bay’s Lupin mine began in 1996. A -15% ramp was extended to the 155-meter level, and 16,011 m of underground drilling were completed before the decline in gold prices forced a suspension of activities at ULU in August 1997. The current owners, Wolfden Resources Inc., drilled 18,569 m in 2004 to increase confidence in the resource blocks. Following this drill program, a revised resource calculated by an independent consultant determined that the ULU deposit contains an inferred/indicated mineral resource of 1,130,000 t grading 11.34 g/t gold (373,748 oz) to the 360-m level. The portal was re-opened in 2005 and a prefeasibility study is underway.